CDCA7 Facilitates Tumor Progression by Directly Regulating CCNA2 Expression in Esophageal Squamous Cell Carcinoma - Li, Hongyi; Weng, Yongjia; Wang, Shaojie; Wang, Fang; Wang, Yanqiang; Kong, Pengzhou; Zhang, Ling; Cheng, Caixia; Cui, Heyang; Xu, Enwei; Wei, Shuqing; Guo, Dinghe; et al. (Frontiers in Oncology, 2021)
Background: CDCA7 is a copy number amplified gene identified not only in esophageal squamous cell carcinoma (ESCC) but also in various cancer types. Its clinical relevance and underlying mechanisms in ESCC have remained unknown. Methods: Tissue microarray data was used to analyze its expression in 179 ESCC samples. The effects of CDCA7 on proliferation, colony formation and cell cycle were tested in ESCC cells. Real-time PCR and western blot were used to detect the expression of its target genes. Correlation of CDCA7 with its target genes in ECSS and various SCC types was analyzed using GSE53625 and TCGA datas. The mechanism of CDCA7 were studied by chromatin immunoprecipitation (ChIP), luciferase reporter assays and rescue assay. Results: The over-expression of CDCA7 promoted proliferation, colony formation, and cell cycle in ESCC cells. CDCA7 affected the expression of cyclins in different cell phases. GSE53625 and TCGA datas showed CCNA2 expression was positively correlated with CDCA7. The knockdown of CCNA2 reversed the malignant phenotype induced by CDCA7 over-expression. Furthermore, CDCA7 was found to directly bind to the cyclin A2 (CCNA2), thus promoting its expression. Conclusions: Our results reveal a novel mechanism of CDCA7 that it may act as an oncogene by directly upregulate CCNA2 to facilitate tumor progression in ESCC.